Percutaneous Biopsy in Evaluation of Lung Nodules - Podbielski, Francis J. (Society of Laparoendoscopic Surgeons, 2004)
Management of an indeterminate pulmonary nodule is a diagnostic challenge that commonly confronts primary care physicians and specialists. Patients often present with this radiographic finding in the course of an unrelated medical evaluation. We examined our institution's experience with percutaneous biopsy of lung nodules to determine the impact of this procedure on overall patient care. Although significant complications are uncommon, the expedience of percutaneous lung biopsy often supplants a surgical opinion prior to initiation of therapy without added diagnostic benefit or cost-savings. Hence, we caution practitioners to use this technique as an adjunct to diagnosis and not a substitute for multidisciplinary care.